Pengembangan Media Praktikum PCT (Paper Chromatography Techniques) Berbasis Android dengan QR Code Technology pada Materi Pemisahan Campuran - Mellyta Uliyandari; Emilia Candrawati; Nurlia Latipah (University of Bengkulu, 2022)
The purpose of this study was to develop an android-based PCT (Paper Chromatography Techniques) practicum media with QR code technology on mixed separation materials to help improve the quality of learning, especially in general chemistry practicum courses. This development is carried out using a 4D (four-D) research design, namely defining, designing, developing, and disseminating. At the definition stage, the formulation of the practicum objectives is carried out, the design stage is carried out by designing practicum media, while at the development stage the practicum media content validation is carried out by media experts and material experts, the dissemination stage is carried out through e-learning at Bengkulu University. The distribution of practicum media is carried out after the media is declared valid by the validator, namely material experts and media experts. The practicum media validation score by material experts is 70 which is in the